Probing individual saturations of crude-oil/brine/mud-filtrate mixtures confined in rocks - Benamsili, Lyès; Hamon, Gérald; Korb, Jean-Pierre (Diffusion Fundamentals, 2013)
We propose a method that allows probing quantitatively the individual saturations of crudeoil/brine/mud-filtrate mixtures during imbibition-drainage experiments on a petroleum rock-system. The experiments have been also performed at different temperature and pressure conditions.